Rheology of Complex Topical Formulations: An Analytical Quality by Design Approach to Method Optimization and Validation - Lucas Chiarentin; Catarina Cardoso; Margarida Miranda; Carla Vitorino (MDPI AG, 2023)
Analytical method validation ensures that a method provides trustworthy information about a particular sample when applied in accordance with the predefined protocol. According to regulatory standards, the rheological characteristics of topically applied semisolid formulations are one of the key elements involved in microstructure equivalence documentation. Therefore, for generic drug product manufacturers, it is a dire need to take a step forward in rheology method development and validation procedures. This paper aims to apply Analytical Quality by Design (AQbD) principles towards the development and validation of rheology methods for topical creams, as complex semisolid formulations. Risk assessment was carried out through an Ishikawa diagram and an estimate failure mode, effects, and criticality analysis (FMECA). Sample application, peltier temperature control, and sample rest time were identified as critical method variables (CMVs), and a 23 full factorial design was applied to understand their impact on rotational, creep recovery and, oscillatory measurements. The development of the method was carried out as per the ICH Q8-Q10, and Q14 guidelines and validated according to ICH Q2 (R2) guideline. The method demonstrated adequate precision (RSD < 15%), as well as selectivity. AQbD provided a comprehensive framework for developing a reliable and effective rheology method for this type of formulation.